Pengaruh Pendidikan Kesehatan Teknik Relaksasi Nafas Dalam Untuk Mengurangi Nyeri Dismenore Terhadap Pengetahuan Siswi SMP - Puspita, Irma Maya (Universitas Muhammadiyah Surabaya, 2024)
Objective: Dysmenorrhea is a condition of pain or pain in the lower abdomen during menstruation that can interfere with the teaching and learning process, which is most often found in female students. Efforts to relieve pain usually only focus on drugs (pharmacology), while non-pharmacological treatment can also be done, one of which is using deep breathing relaxation techniques. This study was to determine the effect of health education on deep breathing relaxation techniques to reduce dysmenorrhea pain on female students' knowledge at SMP Pawiyatan Surabaya. Methods: This study used a quasy experimental design with One Group Pretest-Posttest Design. The number of samples is 75 respondents. The population of this study were all female students at SMP Pawiyatan who were menstruating by purposive sampling. Data collection techniques using knowledge questionnaire sheets and Guttman scales. Data analysis used the Wilcoxon Sign Rank Test; the test results showed an asymp. Sign (2-tailed) value of 0.000 <0.05 so that the data was accepted. Namely, there was an influence between before and after health education on deep breathing relaxation techniques. The results of knowledge before being given education were good at 36%, and after being provided education, they were good at 82.7%. Results: This shows that there is an increase in student knowledge before and after with a difference of 46.7%, and a significant result is obtained of 0.000 <0.05 (p-value = 0.000 <0.05) Conclusion: Ho is rejected, which means there is an influence of technical health education, such as deep breathing relaxation, to reduce dysmenorrhea pain on female students' knowledge at SMP Pawiyatan Surabaya. With this research, it is hoped that female students can implement deep breathing relaxation techniques to reduce dysmenorrhea pain in everyday life.